Smart selection from petri net modeling tools for fast developing a manufacturing system. Issue 1 (31st December 2022) - Lin, Yi-Nan; Yang, Cheng-Ying; Chiou, Gwo-Jen; Wang, Sheng-Kuan; Shen, Victor R.L.; Wang, Yu-Ying; Bui, Hai Hoang; Wang, Jianzhi
Abstract: Petri net (PN) is a well-known graphical and mathematical model that can be used to describe a system quickly and dynamically. Over the last decade, it has provided many applications for academia research and industrial practice, especially, for the system verification and performance evaluation. Compared with other system models, the PN model is easy to implement. Therefore, it can be recommended as an effective way for people to study the model checking and validation. For the purposes of reducing time span to get familiar with PN tools, it is necessary to have an informative guide, providing general information about a PN software tool for system developers. This paper aims to review HiPS, PIPE, and WoPeD tools which are simple, lightweight, and free of charge. Our proposed approach also compares their strengths and limitations with each other to help the system developers determine a suitable PN software tool and shorten the time to markets for their products. Thus, it is truly beneficial to fast develop a manufacturing system.